ICT ASSISTED PROJECT-BASED LEARNING MODEL TO IMPROVE STUDENTS’ CRITICAL THINKING SKILLS - Yeyen Suryani; Entin Jumantini; Iskandar Iskandar; Rani Tania Pratiwi; Vira Siti Fatimah (Universitas Kuningan, 2023)
This study aims to develop students’ learning by employing ICT in a project-based learning (PBL) model to improve students’ critical thinking skills in economics subject. A Research and Development design was applied in this study by using exploratory and quasi-experimental methods with a non-equivalent control group pretest-posttest design. This study involved students of XI IPS class at SMAN 1 Kadugede. The collected data from tests, observations, and focus group discussions were then analyzed using quantitative and qualitative methods. As a result, this study obtained a learning model and learning media in the form of syllabus, lesson plan, teaching materials, observation sheets, and tests for critical thinking skills that can be used in the economics subject at SMAN 1 Kadugede. Besides, this study also proved that the ICT assisted project-based learning (PBL) model is effective in improving students’ critical thinking skills as well as students’ enthusiasm for expressing their opinions, suggestions, and input on the topic being discussed.Keywords: ICT; critical thinking skill; project-based learning.